Cardiorespiratory kinetics: comparisons between athletes with different training habits - Koschate, J.; Gerlich, L.; Wirtz, V.; Thieschäfer, L.; Drescher, U.; Hoffmann, U. (European Journal of Applied Physiology, 2019)
Purpose: Fast muscular oxygen uptake (VO2musc) kinetics are limiting factors for high exercise capacities. It is hypothesized that VO2musc and heart rate (HR) kinetics would be faster in individuals, performing long-distance endurance training (CONT) compared with athletes performing predominantly interval-based sports (INT). Methods: 17 subjects (INT: n = 7, 24 ± 5 years, 183 ± 7 cm, 85 ± 10 kg, 6 ± 3 h of training per week, CONT: n = 10, 37 ± 7 years, 175 ± 9 cm, 69 ± 10 kg, 6 ± 3 h of training per week) completed a treadmill work rate (WR) protocol with pseudo-randomized WR changes with velocities of 6.5 and 9.5 km/h. VO2musc and the respective kinetics were estimated from the measured pulmonary oxygen uptake and HR combined with a circulatory model. Kinetics information were calculated using time series analysis. Higher maxima of the cross-correlation function (CCF) of WR and the respective parameter (VO2musc, HR) indicate faster kinetics responses. Results: The kinetics of HR (INT: 0.23 ± 0.04 vs. CONT: 0.42 ± 0.18; P = 0.001), VO2pulm (0.30 ± 0.05 vs. 0.53 ± 0.20; P = 0.005) and VO2musc (0.31 ± 0.06 vs. 0.53 ± 0.16; P = 0.005) were significantly slower in INT compared with the CONT athletes. Conclusions: It seems that at least in the long-term CONT exercise, training without the need of changing intensities is favorable for fast VO2 and HR kinetics compared with INT exercise including frequently changing intensities.